Analyzing The Impact of Macroeconomic Factors on Stock Market Performance in Asean-5 Countries - Diana Hassan; Chia, Ricky Chee Jiun; Assis Kamu; Ho, Chong Mun (Human Resource Management Academic Research Society, 2024)
The research on factors affecting the stock market index has been thoroughly documented over the years. However, most of this research has primarily focused on macroeconomic aspects within industrialized countries. To address this disparity, this study aims to bridge the gap by investigating the factors influencing the stock market index in emerging countries such as Malaysia, Indonesia, Singapore, Thailand, and the Philippines, utilizing decade-long data from 2012 to 2022. Amid the COVID-19 pandemic that began in December 2019, this research expands the existing literature by exploring the correlations between the stock market indices of the ASEAN-5 countries and key economic indicators, including interest rates, consumer price index, exchange rates, and industrial production indices. The Generalized Method of Moments (GMM) is employed as the estimation procedure using E-views 12, providing a platform for exploring hypotheses and statistical correlations in econometric models, particularly for panel data with monthly observations spanning from January 2012 through December 2022. The research findings highlight a positive and significant association between the ASEAN-5 market index with the indices for consumer price and industrial production. In contrast, the interest rates and exchange rates exhibit a negative correlation coefficient. Consequently, these insightful findings can serve as a robust guideline for efficient management and encourage the adoption of indicators that remain unaffected during global health crisis in the future. Moreover, when making investment decisions, investors should assess their long-term financial goals and risk tolerance and consider sectors that such problems might impact.